Screening for Torture, Asylum, and Trauma among Patients Seeking Care in an Urban Student-Run Free Clinic - Jonathan Pan; Andrew Leader; Eileen Wang; Nicole Ratnapala; Katherine L Garvey; Ramita Gowda; Joe-Ann Moser; AJ Mell; Theodore Pak; Elizabeth Singer; David Thomas; Yasmin Meah (Journal of Student-Run Clinics, 2022)
Introduction: Many immigrants have histories of violence and persecution in their countries of origin that may make them eligible for asylum in the United States. East Harlem Health Outreach Partnership (EHHOP) is a physician-supervised, student-run free clinic (SRFC) of the Icahn School of Medicine at Mount Sinai that serves exclusively uninsured persons, nearly all of whom are immigrants. This study aimed to provide a screening tool to measure the prevalence of self-reported histories of persecution which may be grounds for asylum and connect these patients to appropriate resources such as legal aid and forensic medical services.Methods: The Screening for Torture, Asylum, and Trauma (STAT) questionnaire was developed to screen patients for potential asylum-eligible histories. The questionnaire probed if participants were ever victims of violence or abuse in their countries of origin and the contexts of such violence. Patients screening positive for trauma which may constitute grounds for an asylum claim (“STAT-positive”) were assigned a case manager to oversee referrals to appropriate resources. Changes in demographics between STAT-positive and STAT-negative patients were determined using Fisher Exact Tests and binomial exact calculations to generate P-values and 95% Confidence Intervals (CI), respectively.Results: Of the 86 patients screened, 27 (31%; 95% CI [0.22-0.42]) were STAT-positive. Nineteen (70%) were interested in applying for asylum and 15 (79%) of these patients were successfully referred to legal assistance programs. Seventeen (63%) were already receiving care at EHHOP’s mental health clinic. Conclusion: There is a high prevalence of patients (31%) within the EHHOP SRFC with histories of violence, abuse, persecution, or discrimination which may be grounds for asylum in the United States. Identifying these patients for targeted interventions may have a significant positive impact for these patients.